Analysis of Factors Affecting Student Saving Interest in Bank Mini Smk Muhammadiyah 2 Pekanbaru - Fatma, Fatma; Gimin, Gimin; Suarman, Suarman (FKIP-Universitas Riau, 2020)
This research was motivated by the low interest in saving students at Bank Mini SMK Muhammadiyah 2 Pekanbaru, which was only 36% of the total number of students. The aim of this study is to analyze the factors that influence the students interest in saving at the Mini Bank SMK Muhammadiyah 2 Pekanbaru. This research used descriptive methods. As a result, there is a partial effect of students 'saving knowledge, student saving motivation, student pocket money, and bank services, on students' interest in saving at Bank Mini SMK Muhammadiyah 2 Pekanbaru. As well as the joint effect of student saving knowledge, student saving motivation, student pocket money and bank services on student saving interest. It can be concluded that there is a significant and positive influence on student saving knowledge, student saving motivation, student pocket money, and bank services either partially or jointly towards students' interest in saving at Bank Mini SMK Muhammadiyah 2 Pekanbaru.